Pemerolehan Dan Perkembangan Bahasa Dalam Pendidikan - Dessy Syofiyanti; Lisdiyana; Muhammad Alfian Tuflih; Helina Apriyani; Dian Purnomo (JURNAL ARMADA PENDIDIKAN, 2025)
Language acquisition and development is a fundamental process in human life that begins in infancy and continues to develop throughout life. This study aims to analyze the stages of language acquisition, influencing factors, and theoretical perspectives that explain language development. This study uses a qualitative descriptive approach through literature studies. The results of the study indicate that language acquisition occurs naturally and systematically, influenced by biological, cognitive, and environmental factors. Several theories explain this process, including behaviorism, nativism, cognitivism, and interactionism. This study also highlights the importance of social interaction and stimulation in optimizing language development. This study can be recommended for educators, psychologists, and speech therapists to have an understanding and language acquisition to design effective learning strategies and as effective interventions for individuals with language delays in children.